Underworld. Evolution [videorecording (DVD)] - Wiseman, Len (Underworld films, 2006)
Vampire heroine Selene continues the saga of war between the aristocratic Death Dealers and the barbaric Lycans. The film traces the beginnings of the ancient feud between the two tribes. Selene and her love Michael, the lycan hybrid, try to unlock the secrets of their bloodlines. The tale of action, intrigue and forbidden love takes them into the battle to end all wars as the immortals must finally face their retribution.